Commenda partnership (mudarabah) - an overview - Mohd Noor, Fauziah (TM-Info-Media Sdn. Bhd., 2009)
Mudarabah is an Islamic contract in which one party supplies the capital (money) and the other provides management expertise to undertake a lawful specific business or project. The former is known as the owner of the capital (rabb al-mal) and the latter is refereed to as an agent (mudarib) who actually runs the business. The practice of mudarabah can be traced back through several centuries of Islamic history. It had been applied in trade, agriculture and manufacturing sector. This contract is particularly capable of attracting those potential capable entrepreneurs who are unable to provide any capital to run a business. In other words, this contract could lead to a desirable distribution of income by discouraging concentration of wealth in fewer hands.